Selective Acetalization in Pyridine: A Sustainable 5′-O-(2-Methoxypropyl) Protecting Group in the Synthesis of Nucleic Acid Analogs - Saari, Verneri; Eerola, Aino; Ora, Mikko; Molina, Alejandro Gimenez; Horvath, Andras; Sanghvi, Yogesh S.; Virta, Pasi (AMER CHEMICAL SOC, 2026)
A mixture of 2-methoxypropene and an acid catalyst in pyridine results in an efficient 5 '-O-(methoxyisopropyl) (MIP) acetalization of nucleosides, including 2 '-deoxy, 2 '-OH, 2 '-O-methyl, 2 '-O-methoxyethyl (MOE) and 2 '-F-variants, in 44-77% isolated yields. For the reaction mechanism, we propose a pyridinium 2-methoxyprop-2-yl preassociation complex, which improves regioselectivity for the primary (5 '-OH) over secondary (2 '-OH and 3 '-OH) hydroxy groups. The developed protocol makes the 5 '-O-MIP-acetal an attractive protecting group for the sustainable synthesis of nucleosides and oligonucleotides in solution.